FUNCTIONAL PROPERTIES OF YELLOW PASSION FRUIT BARK (PASSIFLORA EDULIS) IN METABOLIC SYNDROME - Maísa de Lima Claro; Gilmara Péres-Rodrigues; Sabrina Almondes Teixeira (Universidade do Estado do Rio de Janeiro, 2018)
This study aimed to review the literature on the effect of yellow passion fruit bark flour (Passiflora edulis f. flavicarpa) on the metabolic disorders that make up the metabolic syndrome. It is a systematic review, carried out through a bibliographic survey of studies published between 2005 and 2017, indexed in the IBECS, PubMed, CisSaúde, Cochrame, MedCarib, Lilacs, Medline and SciELO databases, as well as in Google Scholar, theses and dissertations databases. The selected studies evaluated the effect of yellow passion fruit bark (P. edulis) on metabolic syndrome parameters. Experimental studies have demonstrated disagreement regarding the hypoglycemic effect and hypotensive effect. In healthy human studies, supplementation with 30 grams of the P. edulis bark flour showed efficiency in glycemic and lipid reduction for LDL and total cholesterol, without toxicity. In studies with people with metabolic syndrome and type 2 diabetes mellitus, hypolipidemic and hypoglycemic effects have also been demonstrated. However, there is still a shortage of publications on the use of P. edulis bark for the treatment of metabolic disorders, and a methodological standardization is necessary to enable its recommendation in clinical practice. DOI: 10.12957/demetra.2018.28957